A vida é uma ópera: a presença da dramaticidade no romance Dom Casmurro de Machado de Assis - Cappelletti, Laura Tereza (2007)
The current dissertation aims to reveal the opera s presence in the novel Dom Casmurro, by Machado de Assis, relating two different languages, the literary and the scenic one, finding out the hidden signification of the feign in the gloomy, character, under the purpose of the Graduate Program on Literature and Literary Critics. The investigation focused some traces, like the presence of the passions (pathos), in scenic arts as well as hybridation of musical and textual languages in the approach to the daily routine lived by Dom Casmurro. It was analysed also the integration of some communication elements typical of the opera gender which can be found in this novel Dom Casmurro such as gesture, music, word, building up the characters through a photographic frame which freezes at the same time as it moves on acts and expressions. The complexity of the novel has required specific theories for the analytical purpose. So, in order to discuss the Dramaticity in the Word it was required to convoke Nietzsche, Gledson, Kerman, Borheim, Coli. In the chapter Between the draw of gestures and the colour of the Words , the dissertation is supported by the theories of Guinsburg, Barthes, Roubine and Delgado. In the third chapter, The Reminded Image and the Musicality in the Word we have found background in Bergson, Bachelard and Seincman. In this analytical an interpretative way, sharing subjectivity with different authors the novel Dom Casmurro, as well as in the opera, revealed itself to be garnished of a memorialistic musicality, supported by memories which interferes in the telling and retelling one s lived experiences. The presence of the opera is observed when it touches the reader s passions when poetry goes thru the spectator linking musical and textual languages. As well as in the cenic 9 arts, Dom Casmurro is a text which is permeated by gestures and words in conflict or not, building up the characters thru his memories and imagination, inviting the reader/spectator to rebuild, Bentinho s life